The Character Education in Learning of Islamic Education: An Analysis of Character Values in Islamic Education Textbook for V Grade Islamic Elementary School - Cahyadi, Ani; Della, Dhia Alfa (SYAMIL: Journal of Islamic Education, 2021)
This research aims to determine and analyze the character values contained in the textbooks of Islamic Education for V grade in Islamic Elementary School. The method used in this research was a content analysis method with a qualitative approach. The source of research data is the PAI (Pendidikan Agama Isam) textbook for Madrasah Ibtidaiyah which is divided into four books, namely Akidah Akhlak, Qur'an Hadith, Fikih, and Sejarah Kebudayaan Islam. The results showed that there are main character values in each book, namely Religius, Nationalis, Mandiri, Gotong Royong, and Integritas scattered throughout the books. Meanwhile, the most dominant character value that appears is Religius with its sub value "Hubungan individu dengan Tuhan". Then, other character values such as Nasionalis and Mandiri are still not widely published in this PAI textbook. Such as Mandiri character that is not in the fikih subject, then nasionalis character which is also not in the subjects of the Qur'an Hadith and Fikih.